Intravesical BCG: where do we stand? Past, present and future. (November 2019) - Hobbs, Catherine; Bass, Edward; Crew, Jeremy; Mostafid, Hugh
High and intermediate risk non-muscle invasive bladder cancer poses a real challenge for treatment. Approximately 70% of bladder cancer presents as non-muscle invasive and 20–25% will progress to muscle invasive disease. Recurrences occur in up to 70% but treatment options are limited. Intravesical bacillus Calmette–Guérin is still considered the bladder sparing treatment of choice despite its well documented pitfalls. This review considers how bacillus Calmette–Guérin has become the recommended treatment, its benefits and risks and the alternative options for treatment. Level of evidence: Not applicable for this multicentre audit.